Skrøbelige liv som værk - Volquartz Lebech, Sofie (Peripeti, 2022)
In this article I discuss how the performance lecture Precarious Life uses artistic and research-based strategies to examine a double metaphor: How terror works as an autoimmune disease, and how an autoimmune disease works as terror in the body. My inquiry should not be seen as a doubling of the artistic process but rather as an unfolding of the conflict between art and research: Does researchbased performance create knowledge, art or both? My strategy in the performance lecture is clear: to say a number of truths in order to create a space for thinking. At the same time, I challenge the authenticity, we connect with knowledge: Does the spectator believe as much in me as in a researcher? Does the spectator believe the autobiographical aspect? What levels of knowledge are communicated to the spectator? In conclusion, I outline the contours of research-based performance.